Preparation of Fatty Amides from Metal Soaps Under Microwave Irradiation - Lee, Yean Kee (2002)
An efficient, high yield method of preparation of pure fatty amides was found through this research. from the 3 - reactant system that consists of fatty sodium soap, a source o f ammonia (or amine) and ammonium chloride, the fatty amides were formed when they were premixed and sealed in a glass vessel and then exposed to microwave irradiation. Primary amides were formed from the reaction of fatty sodium soap, urea or ammonium carbonate and ammonium chloride, whereas secondary amides were formed from the reaction of fatty sodium soap, amines and ammonium chloride. Primary amides successfully synthesized through this method are myristamide, palmitamide, o leamide and stearamide, whereas secondary amides synthesized from this method are N-butyl myristamide, N-butyl palmitamide, N-butyl stearamide, Nhexadecyl myristamide, N-hexadecyl palmitamide, and N-hexadecyl stearamide. Product identification was done through lR, NMR and CHN . The syntheses of myristamide and palmitamide were optimized by varying the irradiation time, reactant ratio and volume of reaction vessels. These optimized conditions were used for other primary amides syntheses. It was found that the best reactant ratio (sodium soap : urea: ammonium chloride) is 1:0.5:1 with 2.5 cm³ volume of reaction vessel when 0.5 g of reactant mixture were irradiated for 9 minutes. In the two or three-reactant systems involving fatty acids and, or sodium soap with urea or ammonium carbonate as the source of ammon ia, the presence or absence of ammonium chloride in these reactant mixtures were studied. The reaction involving soaps required the three-reactant system, where ammonium chloride is present in the reactant mixture. A kinetic study of the synthesis of palmitamide was done. The decomposition of sodium palmitate was found to fit first order kinetics and hence a reaction mechanism was proposed. Palm oil soap was also used in the amide syntheses and mixtures of primary amides were successfully synthesized from the reaction between palm oil soap, urea and ammonium chloride.